2019
DOI: 10.1123/japa.2018-0137
|View full text |Cite
|
Sign up to set email alerts
|

Men on the Move: A Randomized Controlled Feasibility Trial of a Scalable, Choice-Based, Physical Activity and Active Transportation Intervention for Older Men

Abstract: We conducted Men on the Move, a 12-week randomized controlled feasibility trial of a scalable, choice-based, physical activity (PA) and active transportation intervention. Participants were community-dwelling men aged 60 years and older (n = 29 intervention [INT] and n = 29 waitlist control [CON]). Trained activity coaches delivered: (a) one-on-one participant consultations to develop personal action plans for PA and active transportation, (b) monthly group-based motivational meetings, (c) weekly telephone sup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…After 12 weeks of intervention, participants in Men on the Move were more active (i.e., steps, moderate-vigorous PA, and energy expenditure) and more likely to use transit and meet PA guidelines than the control group (Mackey et al, 2019). Men on the Move was deemed feasible based on retention and adherence to the intervention protocol (Mackey et al, 2019). However, similar to others (Anderson et al, 2016), recruiting men to participate proved a challenge.…”
Section: Ctm Delivery and Scale-upmentioning
confidence: 96%
See 1 more Smart Citation
“…After 12 weeks of intervention, participants in Men on the Move were more active (i.e., steps, moderate-vigorous PA, and energy expenditure) and more likely to use transit and meet PA guidelines than the control group (Mackey et al, 2019). Men on the Move was deemed feasible based on retention and adherence to the intervention protocol (Mackey et al, 2019). However, similar to others (Anderson et al, 2016), recruiting men to participate proved a challenge.…”
Section: Ctm Delivery and Scale-upmentioning
confidence: 96%
“…Participants also received transit training (60-min session), free transit passes, and pedometers. After 12 weeks of intervention, participants in Men on the Move were more active (i.e., steps, moderate-vigorous PA, and energy expenditure) and more likely to use transit and meet PA guidelines than the control group (Mackey et al, 2019). Men on the Move was deemed feasible based on retention and adherence to the intervention protocol (Mackey et al, 2019).…”
Section: Ctm Delivery and Scale-upmentioning
confidence: 99%
“…For short-, middle-, and long term follow-up, respectively seven (33,48,52,53,62,64,65), four (42,62,64,65), and seven studies (33,39,42,53,62,64,78) reported interventions with multiple motivational strategies versus active control groups and all studies were pooled. For the comparison to passive control groups, four (31,40,44,68), two (56, 58), and ve studies (32,34,56,58,67) were found for short-, middle-, and long term follow-up, respectively and all studies for short term follow-up were pooled. In the pooled results, for one study we included the goal-setting with mentoring intervention group versus active control group (39).…”
Section: Interventions Using Multiple Motivational Strategiesmentioning
confidence: 99%
“…In three studies, the prede ned in-and exclusion criteria were not targeted to older adults at all(43, 76,79). Of all studies, 22 studies reported additional in-and exclusion criteria regarding functional mobility and/or health parameters (additional to or other or than being inactive)(31-34, 40, 42, 45, 47, 51, 53, 56-58, 60, 62-64, 71, 73, 74, 77, 79).Intervention duration ranged from 2.5 weeks to 12 months of which the majority (13 studies) had a duration of 12 weeks(31,33, 36,40,43,44, 46, 60, 63, 64, 69,77, 78). In three studies the intervention duration varied and depended on the need and physical functioning of the patient(29,30, 65).…”
mentioning
confidence: 99%
“…This wide range of benefits of AT for societies motivates policymakers and urban planners to identify factors and attributes that contribute to a higher level of AT modes' usage [12]. To this end, several studies were conducted to identify the influencing factors on the usage of AT modes by general and special group populations such as children, school children, women, and seniors [13][14][15][16][17][18][19][20][21]. However, some special groups, such as employees, attracted less attention from academia in relation to the use of AT modes.…”
Section: Introductionmentioning
confidence: 99%